Programowa niechęć do państwa jako kwintesencja zjawiska identyfikacji narodowej wśród Kurdów tureckich – analiza głównych przejawów nacjonalizmu kurdyjskiego w Turcji - Szkudlarek, Magdalena (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2012)
The aim of this article is to present a comprehensive analysis of the phenomenon of Kurdish nationalism and identity in Turkey. An emphasis will be placed on aspects such as the lack of acceptance of Kurdish nationalists for state-oriented attitudes among some Kurds, the lack of acceptance for the Turkish government’s pro-Kurdish decisions and abusing of tragic Turks and Kurds’ past by both sides of the con-flict in order to win the propaganda war. The groundless conviction that “Kurdish nationalism” and “ PKK terrorism” is the same thing leads to misunderstanding that terror is the only indication of showing Kurdish identity. The true complexity of this phenomenon will be presented in this article.
Aversion to the State as a Gist of National Identifaction's Phenomenon Among Turkish Kurds - the Analisys of Main Symptoms of Kurdish Nationalism in Turkey
Keywords: Kurdowie; Turcja; Nacjonalizm